1999
DOI: 10.1017/s0317167100000421
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Opening of the Blood-Brain Barrier Following Transient Focal Ischemia: Effects of Hypothermia

Abstract: Objective: Tracer constants (K i ) for blood-to-brain diffusion of sucrose were measured in the rat to profile the time course of blood-brain barrier injury after temporary focal ischemia, and to determine the influence of post-ischemic hypothermia. Methods: Spontaneously hypertensive rats were subjected to transient (2 hours) clip occlusion of the right middle cerebral artery. Reperfusion times ranged from 1.5 min to 46 hours, and i.v.3 H-sucrose was circulated for 30 min prior to each time point (1h, 4h, 22h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
123
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(136 citation statements)
references
References 23 publications
8
123
1
4
Order By: Relevance
“…34 In a focal cerebral ischemia study in rats, hypothermic treatment during the first six hours of reperfusion reduced infarct volume and the late opening of the blood-brain barrier. 35 The present study demonstrates that mild hypothermia induced before CA is associated with a reduction in AQP4 protein expression in the cerebral cortex.…”
Section: Discussionsupporting
confidence: 56%
“…34 In a focal cerebral ischemia study in rats, hypothermic treatment during the first six hours of reperfusion reduced infarct volume and the late opening of the blood-brain barrier. 35 The present study demonstrates that mild hypothermia induced before CA is associated with a reduction in AQP4 protein expression in the cerebral cortex.…”
Section: Discussionsupporting
confidence: 56%
“…This leads to a subsequent increase in cerebral edema; however, the processes involved in the hypoxia-induced BBB permeability are not completely understood. Work in animal models of stroke has identified that there is a biphasic leakage of the BBB, with an early opening within hours following hypoxia/ischemia, followed by a refractory phase and then a second opening the next day (Kuroiwa et al 1985;Huang et al 1999). In addition, analysis in transgenic models has identified that there are stepwise alterations in the BBB, with an increase in transcytosis observed first followed by alterations in the TJs (Knowland et al 2014).…”
Section: Modulation Of the Bbb Following Hypoxia/ Ischemia And In Strokementioning
confidence: 99%
“…12 Cells injured by ischemia essentially have 3 options: become necrotic, undergo apoptosis, or recover. 12 The theoretical benefit of therapeutic hypothermia is that it combats injury by reducing cerebral edema, disruption of the blood brain barrier, 13 and free radical production as well as by stabilizing membranes. 10,14 Therapeutic hypothermia is also thought to reduce excitatory neurotoxic effects caused by impaired glutamate reuptake 10,15,16 and inflammatory cytokine release, specifically interleukins 1 and 6 and tumor necrosis factor-α.…”
Section: Discussionmentioning
confidence: 99%